Merkel cell carcinoma: multiple primary skin lesions in the lower limb - Bruna Margatho Elias; Giovanna Curi Campos; Hudson Dutra Rezende; José Roberto Paes Almeida; Karla Calaça Kabbach Prigenzi; Sandra Lopes Mattos Dinato (Sociedade Brasileira de Dermatologia (SBD), 2022)
Merkel cell carcinoma is a rare and aggressive neuroendocrine skin tumor usually presenting as a single lesion in the head or neck region. We report a case of atypical topography and presentation, with multiple and simultaneous tumors on the left leg of rapid progression associated with palpable inguinal lymphadenopathy and diagnostic confirmation by histopathology and immunohistochemistry. Exeresis of the left inguinal lymph node and skin lesions with a safety margin was performed.